Estudio de captación y bioacumulación de compuestos farmacéuticamente activos en cultivo de Lactuca sativa y evaluación de sus posibles efectos en las características morfológicas de la planta (2021)
It has been shown that pharmaceutically active compounds released in agroecosystems are absorbed and accumulated in the edible parts of crop plants. Using a simulated culture under controlled conditions, the present study aimed to evaluate the absorption and bioaccumulation of three common pharmaceutically active compounds (Diclofenac, Sulfamethoxazole and Losartan) applied individually and in mixture in Lactuca sativa roman crop, and the effects mediated by these compounds on the quality attributes of the leafs plant. Ultrasound assisted solid phase extraction technique and high-performance liquid chromatography was used identified and quantify these compounds in lettuce leaves. Absorption of sulfamethoxazole and losartan was not observed, while diclofenac was detected in concentrations of 0.0372 ng/g. The compounds evaluated and applied at different concentrations significatively affected (lower values) the attributes of the plant such as sugars, humidity, and chlorophyll. On the other hand, it is suggested to continue carrying out studies related with establishment the mobility of pharmaceutical compounds in the plant, their possible metabolization and the probable transformation products of the three pharmaceutical compounds used and of those that may be found in irrigation water samples in crops at field level.